Basic Tutorial on Sliding Mode Control in Speed Control of DC-motor - Hari Maghfiroh; Augustinus Sujono; Musyaffa' Ahmad; Chico Hermanu Brillianto Apribowo (Universitas Sebelas Maret (UNS), 2020)
One technology to support production speed is electric motors with high performance, efficiency, dynamic speed and good speed responses. DC motors are one type of electric motor which is used in the industry. Sliding Mode Control (SMC) is the robust non-linear control. The basic theory regarding SMC is presented. The SMC design which is implemented is the speed control of the DC motor is analyzed. The controller is implemented in simulation using MATLAB / Simulink environment. The step response and signal tracking test unit are carried out. The results show that SMC has a better performance compare to PID which is faster settling time and no overshoot and undershoot.